Water Sensitive Urban Design in Existing Urban Settings: Case Study of Dry Detention Pond in Kuching City - Mah, D.Y.S.; Salehe, A.H.M.; Putuhena, F.J. (Springer Singapore, 2014)
This paper is intended to investigate the potential of dry detention pond in long-established urban settlements in Kuching City. Such pond is inserted to a typical terrace housing estate by means of computer modelling using SWMM software. The initial outputs of model are to identify occurrence of positive altered runoff patterns. Such modelling results provide a tool quantitatively to measure the probable use of the proposed measures to improve the existing urban drainage system.